Pengaruh Model Pembelajan Picture And Picture Terhadap Penguasaan Kompetensi Pengetahuan IPS Siswa Kelas V SD Gusus Raden Ajeng Kartini - Pande Komang Novi Anggreni (Cetta: Jurnal Ilmu Pendidikan, 2018)
IPS knowledge competence score analyzed by matching technique, by matching the value of each student's prates. The results showed that there are significant differences in the competence of IPS knowledge between students who were taught using the model of Picture and Picture learning with students who were taught by Conventional learning. The data of IPS knowledge competence mastery was analyzed using t-test. This is seen from the analysis that the value of tcount is greater than ttable that is 4,816> 2,000 at the level of significance 5% with the average score of knowledge competence competence of experimental class higher than control class that is equal to 81,00> 70,26. Based on these findings, it can be concluded that there is the influence of learning models Picture and Picture on the mastery of the knowledge competence of class IPS students Class of Raden Ajeng Kartini School Year 2016/2017.